PENILAIAN KEPUASAN DENGAN MODEL END USER COMPUTING SATISFACTION BAGI PENGGUNA APLIKASI FINANCIAL TECHNOLOGY (Studi Kasus Bagi Pengguna Aplikasi LinkAja) - Lambang Wahyu Aji; Ida Ayu Kade Rachmawati Kusasih (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This research was conducted to determine the effect of content, accuracy, format, timelines and ease of use on fintech-based application satisfaction, in this case used a fintech-based application called LinkAja as material for research. This research is quantitative in nature and data is obtained through questionnaires distributed through the online media WhatsApp. The samples taken were 60 respondents using non-probability sampling technique, namely convience sampling, while the data analysis technique used hypothesis test, classical assumption test, reliability test, and validity test. The results of this study indicate that the content and format variabels have a significant effect on user satisfaction, while the variabels of accuracy, timelines and ease of use have no significant effect on user satisfaction of the LinkAja application.  The implication is that in order to increase user satisfaction, it is hoped that the company will always maintain quality and innovate its features as well as beautify its appearance by following the latest trends in order to compete against other similar applications.